Cyber inevitability and privacy in the design of interior spaces (Al-Academy, 2023)
Interior design was affected by intellectual and technical changes and developed with it through new design features. There is no doubt that the information age has a great impact on the speed of successive technological development, so that it has become a part whose impact on the individual and his orientations in particular, and on the privacy of contemporary society in general, and because interior design is a reflection of the civilization of peoples and the spirit of These techniques have become an integral part of the interior designer's tools to formulate a new thought in the design process that keeps pace with these changes, so design products that are not linked to clear intellectual rules and models appeared, characterized by ambiguity in defining their identity through strangeness and unfamiliarity. And because the close relationship between technology and civilization as a duality expresses the extent of the development and upgrading of society at the level of the individual’s environment in particular and the social environment in general, it is necessary to focus on the feature of technological spaces and its impact on the privacy of the civilization of contemporary society and its implications at the level of intellectual and applied patterns in interior design. Spaces are represented by cyberspaces that depend on the extent of reason and behavior in the context of interaction between man and technology offered by globalization and the resulting effects that open new horizons and real challenges for the future. To include the social conditions that produced it, and therefore it cannot be isolated from the value system that surrounds these conditions and the social and civilizational changes that may result from their application, such as the disappearance of the borders between the technological and traditional worlds.